Ophthalmologic emergencies: what every doctor needs to know - Cardoso Filho, Antero Pinto; Costa, Luísa Canesin Dourado Figueiredo; Rocha, Eduardo Melani (Medicina (Ribeirao Preto), 2022)
Acute ophthalmic complaints represent an important portion of emergency medical care. This review aims to serve as a guide for basic medical evaluation in the ophthalmological patient, with the suggestion of tools that assist in the clinical eye evaluation, including red eye complaints, loss of vision and trauma, with their respective diagnoses and treatment basis.